Pelatihan Penyusunan Harga Pokok Produk dan Laporan Laba Rugi UMKM di Lampung - Gamayuni, Rindu Rika; Octary, Ayu Dwiny; Nurdiono, Nurdiono (Jurnal Abdimas Multidisiplin, 2024)
Purpose: Many MSMEs are unable to properly prepare and analyze product cost prices and profit and loss reports. The aim of this PKM is to increase knowledge and understanding in determining efficient product cost prices and preparing profit and loss reports for micro, small, and medium-sized enterprises (MSMEs). Methodology/Approach: The methodology consisted of several stages: 1. initial stage (situation analysis and socialization of community services), 2. implementation stage (training in calculating the cost of production and preparing profit and loss reports); 3. Evaluation stage (pretest, posttest, monitoring, and evaluation of results). The training participants were MSMEs in Lampung Province, with production businesses including honey, chips, coffee, herbal drinks, frozen food, handicrafts, soap, spices, kitchen necessities, and pastries. Results: As a result of the PKM, MSME participants can prepare product costs and profit and loss reports for their respective businesses, which can be used to analyze costs to be efficient and generate maximum income. Limitations: MSME actors lack knowledge in classifying and analyzing production costs and determining the correct cost of production. Contribution: After this training, the MSME participants had a strategy to manage their business well and increase income and streamline production or operational costs incurred.